2020
DOI: 10.1016/j.amepre.2019.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Discrimination and Trajectories of C-Reactive Protein: The Jackson Heart Study

Abstract: Introduction: Perceiving discriminatory treatment may contribute to systemic inflammation, a risk factor of cardiovascular pathophysiology. This study evaluated the association of self-reported discrimination with changes in high−sensitivity C-reactive protein and the mediating role of adiposity. Methods: The sample included 5,145 African-Americans, aged 21−92 years, in the Jackson Heart Study. Everyday, lifetime, and burden from perceived discrimination comprised primary predictors in 3 sets of multivariable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Sims et al found that men participating in the JHS with higher levels of lifetime and everyday discrimination had lower high-sensitivity C-reactive protein levels. As noted in their study, this finding may be the result of the relatively small male population in the study and the fact that the JHS male cohort – that is, older, lower SES, and Black – are underrepresented in epidemiologic research [ 54 , 55 ]. Other studies of stress and CVD have focused on employment-related stressors and noted that high work-related effort with low job control/rewards may negatively impact cardiovascular health [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sims et al found that men participating in the JHS with higher levels of lifetime and everyday discrimination had lower high-sensitivity C-reactive protein levels. As noted in their study, this finding may be the result of the relatively small male population in the study and the fact that the JHS male cohort – that is, older, lower SES, and Black – are underrepresented in epidemiologic research [ 54 , 55 ]. Other studies of stress and CVD have focused on employment-related stressors and noted that high work-related effort with low job control/rewards may negatively impact cardiovascular health [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low-income status and smoking activity contributed most to elevated CRP levels among older Black males, whereas obesity mainly contributed to elevated CRP levels in older Black females ( 11 ). Moreover, self-reported daily and lifetime discrimination by Blacks/African Americans (AA) correlated with increased CRP levels ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies were observational (Table 1 ); thus, causal effects cannot be determined. However, nineteen longitudinal studies [ 34 , 36 41 , 48 50 , 52 , 55 , 56 , 90 , 100 , 104 , 108 , 112 , 115 ], seven quasi-experimental studies [ 60 , 64 , 70 , 75 , 77 , 111 , 118 ], and two randomized controlled trials [ 80 , 110 ] provide supporting evidence for temporality and causation. Results of these studies were consistent with the cross-sectional findings; however, some observational studies found positive associations for African American women but not men [ 85 ] and an increase in diastolic but not systolic blood pressure [ 61 , 72 ].…”
Section: Discussionmentioning
confidence: 99%